PRAKTIK PENDIDIKAN KARAKTER BAGI ANAK BERKEBUTUHAN KHUSUS DI SD MUHAMMADIYAH KOTA MADIUN - Rosyida Hanifa Zara'; Oksiana Jatiningsih (Universitas Negeri Surabaya (Unesa), 2022)
This qualitative study aims to describe: practices, problems, and character handling solutions for children with special needs at SD Muhammadiyah Kota Madiun. Data were collected through a google form questionnaire, with a total of seven subjects including the principal, vice principal, coordinator of children with special needs, two psychologists, and two classroom teachers. In addition, there were 12 teachers as additional subjects. The results showed that in Muhammadiyah Elementary School, Madiun City, there were 15 children who had special disabilities that required special assistance to the spesial needs children. The problems faced in the character education process for children with special needs are: (1) the difficulty of controlling children; (2) Lack of parental attention to their children. This can be overcome through good cooperation between teachers, psychologists, and shadow teachers. Within that framework, the efforts made are (1) the application of teacher creativity in the implementation of learning and interaction with children. Activities carried out in instructional and non-instructional activities within innovative, creative, and joyful learning such as conditioning in learning through posters. (2) Implementation of the Individual Learning Program (PPI). Keywords: Character education, ABK, Muhammadiyah Elementary School Madiun City.